A twisted macrocyclic hexanuclear palladium complex with internal bulky coordinating ligands. Issue 17 (11th January 2019) - Nagai, Akira; Nakamura, Takashi; Nabeshima, Tatsuya
Abstract : A macrocyclic hexanuclear palladium complex, which accumulates coordination sites on metals inside the cavity, was found to take a uniquely-twisted conformation when six molecules of a bulky pyridine derivative coordinated to the palladium. Abstract : A macrocyclic hexanuclear palladium complex, which accumulates coordination sites on metals inside the cavity, was synthesized. The macrocycle was found to take a uniquely-twisted C 2 -symmetric conformation when six molecules of a bulky pyridine derivative coordinated to the palladium.